2015
DOI: 10.1080/23273798.2015.1083114
|View full text |Cite
|
Sign up to set email alerts
|

Differential allocation of attention during speech perception in monolingual and bilingual listeners

Abstract: Attention is required during speech perception to focus processing resources on critical information. Previous research has shown that bilingualism modifies attentional processing in nonverbal domains. The current study used event-related potentials (ERPs) to determine whether bilingualism also modifies auditory attention during speech perception. We measured attention to word onsets in spoken English for monolinguals and Chinese-English bilinguals. Auditory probes were inserted at four times in a continuous n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
2
6
0
4
Order By: Relevance
“…In this study we also explored the power of the same variables but from another perspective, ascertaining how the school can affect the predictive value of L1, nationality and SES as regards performance on tests. These data are consistent with studies by Astheimer, Berkes and Bialystok (2016), by Kim (2009), by Marinova-Todd and Zhao (2010), and by Verhoeven (2007), which found that for awareness and phonemic manipulation tests the L1 of non-native learners was evident as an influence and cognitive strategy (transfer). Thus, to answer Hypothesis 2, we conducted univariate analyses that allowed us to see that when the type of school effect is controlled.…”
Section: L1 and Nationality: Are They Such Correctsupporting
confidence: 92%
“…In this study we also explored the power of the same variables but from another perspective, ascertaining how the school can affect the predictive value of L1, nationality and SES as regards performance on tests. These data are consistent with studies by Astheimer, Berkes and Bialystok (2016), by Kim (2009), by Marinova-Todd and Zhao (2010), and by Verhoeven (2007), which found that for awareness and phonemic manipulation tests the L1 of non-native learners was evident as an influence and cognitive strategy (transfer). Thus, to answer Hypothesis 2, we conducted univariate analyses that allowed us to see that when the type of school effect is controlled.…”
Section: L1 and Nationality: Are They Such Correctsupporting
confidence: 92%
“…The latter showed better results (Table 3), which corroborates the findings of another study, also performed in the south of Brazil, which reported the advantage of bilingual individuals 3 . These findings also emphasize that inhibitory control and attention are much more evident in bilinguals 9,24 , which influences performance in the SSW.…”
Section: Discussionsupporting
confidence: 56%
“…Some studies suggest that bilingual experience enhances executive functions, including attentional control (Bialystok, Craik & Luk, 2012). In this case, bilinguals and monolinguals would differ in the PN effect; however, it is unclear whether better attentional control would result in a larger or a smaller effect (but see Astheimer, Berkes & Bialystok, 2016).…”
Section: The Present Studymentioning
confidence: 99%